ANATOMICAL VARIATIONS OF RENAL VESSELS: IMPACT ON SURGICAL OUTCOMES IN PUJ OBSTRUCTION - Irshad Khan; Samiul Haq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
ABSTRACT Background: Pelvic-Ureteric Junction (PUJ) obstruction is a frequent urological pathology associated with anatomical variations in renal vessels in particular accessory renal arteries or early arterial branching. These anatomic variations may culminate in extrinsic compression of the PUJ and poses a major challenge in surgery. Aim: Thus, the objective of this work will be to assess the frequency of the renal vascular anomalies and their implications for the PUJ obstruction surgery. Method: Retrospective cohort study was undertaken on patients with PUJ obstruction diagnosis. Renal vascular anomalies were identified using imaging techniques before the surgery such CT angiography and magnetic resonance angiography. Laparoscopic or open pyeloplasty was performed, and the specific surgical technique used for each patient was modified based on the presence of vascular abnormalities. The comorbidity of HA, symptom improvement, complications in the postoperative period, and further management were assessed according to the presence or absence of VAs. Results: The renal vascular anomalies were detected in 35% of the study population with the most common being an accessory renal artery. Technique-specific success rates indicate that although patients with vascular anomalies took longer to operate on and suffered higher rates of minor complications, procedures such as the vascular hitch, were just as successful as those in patients with no vascular anomalies. Further, follow up showed that most of the patients maintained resolution of symptoms for the long term. Conclusion: Abnormalities of the renal vascular system play a crucial role in both the morpho physiology of PUJ obstruction and its surgical approach. A thorough preoperative imaging of patients is crucial in diagnosis as well as in the planning for the surgery. It is possible to get positive results by developing individual orientations on such peculiarities. More studies are required to fine-tune the approach on more difficult problem scenarios.